2005
DOI: 10.1080/15434610590956895
|View full text |Cite
|
Sign up to set email alerts
|

Acculturative Stress, Violence, and Resilience in the lives of Mexican-American Youth

Abstract: This article explores how Mexican-American youth experience stress and trauma in a variety of arenas. Such youth utilize their energy, creativity, and resilience in order to cope with cultural tensions that arise from acculturative processes, role conflicts with family and peers, school challenges, and identity formation processes. Violence, in the form of internalized colonialism, external oppression, and actual violent acts (e.g., gang fights, suicides, and physical and=or sexual abuse), can be a major risk … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
17
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 32 publications
2
17
0
Order By: Relevance
“…By bullying the recently immigrated students, the Mexican American students assert their dissimilarity to a group that is more vulnerable to discrimination. These findings are consistent with other studies that portrayed the conflicts and discrimination that are present within an ethnic group due to different levels of acculturation and feeling superior over the more or less acculturated group (Holleran & Jung, 2005;Niemann et al, 1999;Qin et al, 2008;Waters, 1991). Romero and Roberts (2003) indicated that stress may result from cultural conflicts within an ethnic group due to the different levels of acculturation.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…By bullying the recently immigrated students, the Mexican American students assert their dissimilarity to a group that is more vulnerable to discrimination. These findings are consistent with other studies that portrayed the conflicts and discrimination that are present within an ethnic group due to different levels of acculturation and feeling superior over the more or less acculturated group (Holleran & Jung, 2005;Niemann et al, 1999;Qin et al, 2008;Waters, 1991). Romero and Roberts (2003) indicated that stress may result from cultural conflicts within an ethnic group due to the different levels of acculturation.…”
Section: Discussionsupporting
confidence: 94%
“…It appears that Mexican American students have acculturated into the dominant American culture and now discriminate against Mexican immigrant students. Results are also consistent with Holleran and Jung's (2005) findings, which showed that there are frequent clashes and prejudice exists between more and less acculturated groups. In a school environment, these conflicts arise and take the shape of verbal, physical, and relational bullying.…”
Section: Discussionsupporting
confidence: 94%
“…The lower rate of ACEs among Hispanics may explain the insignificant effects if, as suggested above, a threshold exists. It is also possible that Hispanic youth in the State of Florida are better able to cope with these stressors and traumas in a way that does not translate into crime and violence, that is, they are more resilient (Holleran & Jung, 2005). Accordingly, future research should explore the potential for both individual and cultural factors to moderate the relationship between ACEs and the negative life events often being connected to them.…”
Section: Discussionmentioning
confidence: 99%
“…Little is known about more moderate forms of interpersonal violence (e.g. physical and nonphysical types of aggression toward peers) despite that fact that it is more prevalent (Bui & Thongniramol, 2005; Feldmeyer, 2009; Holleran & Jung, 2005; Kim & Goto, 2000; Lee, Martinez, & Rodriguez, 2000; Martinez, 1997, 2000; Peguero, 2008; Reiboldt, 2001; Rodriguez & Brindis, 1995). Moderate interpersonal violence is an important public health problem with serious physical and emotional consequences (Bui & Thongniramol, 2005; Centers for Disease Control & Prevention, 2009; Gupta et al, 2009; Rodriguez & Brindis, 1995; Silverman, Decker, & Raj, 2007; Smokowski & Bacallao, 2006; Smokowski et al, 2009).…”
mentioning
confidence: 99%